La comunicazione del rischio chimico. Sperimentazione e valutazione nelle scuole di Roma - De Cataldo, Alessandra; Fasanella, Antonio; Maggi, Manlio (Il riccio e la volpe - Open Access, 2016)
The book contains the results of a research on the outcomes of a communication campaign of the risks related to exposure to chemicals. The initiative, aimed at students of 3rd, 4th and 5th high school classes of the City of Rome, explored the initial level of skills and knowledge on the chemical hazard, and then assessed the increase as a result of an information campaign conducted by experts of Istituto Superiore per la Protezione e la Ricerca Ambientale (ISPRA), in order to spread knowledge on the subject and form a group of aware young citizens.